Reformation thought : an introduction - McGrath, Alister E., 1953- (Malden, MA : Wiley-Blackwell, 2012)
'Reformation Thought, 4th edition offers an ideal introduction to the central ideas of the European reformations for students of theology and history. Written by the bestselling author and renowned theologian, Alister McGrath, this engaging guide is accessible to students with no prior knowledge of Christian theology. The revised edition reflects the very latest scholarship, and explains its importance for our understanding of the reformation. It now includes extended sections on the Catholic reformation, the counter-reformation, and the role of women during this period, as well as contextual material on the social and political background to the reformation. Additional student-friendly features include images, updated bibliographies, a glossary, and a chronology of political and historical ideas. This latest edition retains all the features which made the previous editions so popular with readers, while McGrath's revisions have ensured it remains the essential student guide to the subject'--
Includes bibliographical references and index.
Keywords: Theology, Doctrinal -- History -- 16th century; Reformation